The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1136/bmj.295.6606.1093
|View full text |Cite
|
Sign up to set email alerts
|

Micrometastases in bone marrow in patients with primary breast cancer: evaluation as an early predictor of bone metastases.

Abstract: The bone marrow of 307 patients with primary breast cancer was examined for tumour cells by immunocytochemistry using an antiserum to epithelial membrane antigen. Micrometastases were found in 81 cases (26.4%) and their presence was related to various poor prognostic factors: spread to lymph nodes, vascular invasion, T stage, and pathological size. The median duration of follow up was 28 months. Seventy five patients relapsed, 60 at distant sites. Of these 60 patients, 26 had micrometastases detected at presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
37
1
2

Year Published

1991
1991
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(43 citation statements)
references
References 18 publications
3
37
1
2
Order By: Relevance
“…TCD in bone marrow correlates with prognosis in patients with primary breast cancer. Other authors obtained similar results (Mansi et al, 1987;Schlimok et al, 1987;Untch et al, 1988;Osborne et al, 1991). The bone marrow of 80% of patients with subsequent metastasis was TCD positive at the time of first diagnosis (Diel et al, 1996).…”
Section: Discussionsupporting
confidence: 62%
“…TCD in bone marrow correlates with prognosis in patients with primary breast cancer. Other authors obtained similar results (Mansi et al, 1987;Schlimok et al, 1987;Untch et al, 1988;Osborne et al, 1991). The bone marrow of 80% of patients with subsequent metastasis was TCD positive at the time of first diagnosis (Diel et al, 1996).…”
Section: Discussionsupporting
confidence: 62%
“…The percentage of tumour cell-positive patients (38%) in this study is slightly higher than in our earlier publications (Harbeck et al, 1987;Untch et al, 1988) or the percentage reported by some other groups (Mansi et al, 1987;Schlimok et al, 1987;Porro et al, 1988;Ellis et al, 1989;Diel et al, 1990). One explanation might be an improved detection rate by using an antibody cocktail instead of a single monoclonal antibody.…”
Section: Discussioncontrasting
confidence: 53%
“…Thus, they were able to rule out possible tumour cell spread due to surgical manipulation. Yet another argument against a merely artificial spread of tumour cells by surgical intervention is the fairly constant percentage of tumour cell detection in the literature, whether bone marrow aspirates are taken immediately before (Mansi et al, 1987;Porro et al, 1988;Cote et al, 1991) or after (Harbeck et al, 1987;Diel et al, 1992) primary surgery. In our opinion, multiple aspiration sites as well as the use of cocktails of monoclonal antibodies are likely to play a far more important role in an increased detection rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future trials will establish the impact of this form of primary systemic treatment on mortality from this disease. However, we feel that improved survival may result since it will be possible to select adjuvant therapy more accurately (a) selecting those that are endocrine sensitive using immunocytochemical tests, (b) by evaluating sensitivity of the primary tumour and thus response of micrometastases (McClelland et al, 1986;Coombes et al, 1986;Mansi et al, 1987).…”
Section: Discussionmentioning
confidence: 99%